Biochemical characterization of L-asparaginase isoforms from Rhizobium etli—the boosting effect of zinc - Sliwiak, Joanna; Worsztynowicz, Paulina; Pokrywka, Kinga; Loch, Joanna I.; Grzechowiak, Marta; Jaskolski, Mariusz (Frontiers in Chemistry, 2024)
L-Asparaginases, divided into three structural Classes, catalyze the hydrolysis of L-asparagine to L-aspartic acid and ammonia. The members of Class 3, ReAIV and ReAV, encoded in the genome of the nitrogen fixing Rhizobium etli, have the same fold, active site, and quaternary structure, despite low sequence identity. In the present work we examined the biochemical consequences of this difference. ReAIV is almost twice as efficient as ReAV in asparagine hydrolysis at 37°C, with the kinetic KM, kcat parameters (measured in optimal buffering agent) of 1.5 mM, 770 s-1 and 2.1 mM, 603 s-1, respectively. The activity of ReAIV has a temperature optimum at 45°C–55°C, whereas the activity of ReAV, after reaching its optimum at 37°C, decreases dramatically at 45°C. The activity of both isoforms is boosted by 32 or 56%, by low and optimal concentration of zinc, which is bound three times more strongly by ReAIV then by ReAV, as reflected by the KD values of 1.2 and 3.3 μM, respectively. We also demonstrate that perturbation of zinc binding by Lys→Ala point mutagenesis drastically decreases the enzyme activity but also changes the mode of response to zinc. We also examined the impact of different divalent cations on the activity, kinetics, and stability of both isoforms. It appeared that Ni2+, Cu2+, Hg2+, and Cd2+ have the potential to inhibit both isoforms in the following order (from the strongest to weakest inhibitors) Hg2+ > Cu2+ > Cd2+ > Ni2+. ReAIV is more sensitive to Cu2+ and Cd2+, while ReAV is more sensitive to Hg2+ and Ni2+, as revealed by IC50 values, melting scans, and influence on substrate specificity. Low concentration of Cd2+ improves substrate specificity of both isoforms, suggesting its role in substrate recognition. The same observation was made for Hg2+ in the case of ReAIV. The activity of the ReAV isoform is less sensitive to Cl− anions, as reflected by the IC50 value for NaCl, which is eightfold higher for ReAV relative to ReAIV. The uncovered complementary properties of the two isoforms help us better understand the inducibility of the ReAV enzyme.